2008
DOI: 10.1186/1471-2474-9-135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rat osteotomy model with impaired healing

Abstract: Background: Delayed union or nonunion are frequent and feared complications in fracture treatment. Animal models of impaired bone healing are rare. Moreover, specific descriptions are limited although understanding of the biological course of pathogenesis of fracture nonunion is essential for therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
0
23
0
2
Order By: Relevance
“…This discrepancy may be due to the fact that the model used by Brown et al [11] consisted of an open osteotomy with rotationally instable fixation, while in the present study we performed a closed fracture with a rotationally more stable fixation. In fact, rotationally unstable fixed osteotomies may not be ideal to study the process of fracture repair, because they are associated with delayed healing [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to the fact that the model used by Brown et al [11] consisted of an open osteotomy with rotationally instable fixation, while in the present study we performed a closed fracture with a rotationally more stable fixation. In fact, rotationally unstable fixed osteotomies may not be ideal to study the process of fracture repair, because they are associated with delayed healing [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely the reason that single growth factor therapies of fixed dose and limited duration exhibit limited therapeutic success: bone heals instead with a complex hierarchy of processes that involve complex pathways and dynamic dosing of multiple factors in close coordination. Clinically relevant small and large animal models of delayed bone healing are being utilized in an effort to better understand the cascades that lead to a healing delay or to non-unions [6770]. Data from studies utilizing these animal models have indicated that all bone healing stages still occur during delayed bone healing, albeit with a difference in temporal onset and spatial distribution of callus tissue compared to normal healing subjects [71].…”
Section: Endogenous Mechanisms In Secondary Bone Healingmentioning
confidence: 99%
“…Numerous animal models of nonunion fracture have been developed, to understand the pathogenesis of this condition and improve treatment [9][10][11][12][13][14][15]. Nevertheless, most of those models create purely mechanical disturbances, but not the metabolic pertubations that result in atrophic nonunion fracture [9].…”
Section: Introductionmentioning
confidence: 98%